2020
DOI: 10.1055/s-0040-1709497
|View full text |Cite
|
Sign up to set email alerts
|

Discharging Medically Complex Infants with Supplemental Nasogastric Tube Feeds: Impact on Neonatal Intensive Care Unit Length of Stay and Prevention of Gastrostomy Tubes

Abstract: Objective The aim of this study is to evaluate the feasibility, safety, and efficacy of discharge with supplemental nasogastric tube (NGT) feeds in medically complex infants. Study Design Cohort study of 400 infants enrolled in the Transitional Medical Home (TMH) program at Duke University Level IV neonatal intensive care unit from January 2013 to 2017. Results Among 400 infants enrolled in the TMH, 57 infants were discharged with an NGT. A total of 45 infants with a variety of diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…9 More programs are now reporting positive experiences with home NG programs. [9][10][11][12]19 Our study adds to this growing literature by comparing outcomes for infants discharged with G tubes and NG tubes to a unique reference group of infants who could have been discharged with home NG feeds but who instead remained in the NICU until achieving full oral feeding. Another unique feature of our study was the inclusion of patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 More programs are now reporting positive experiences with home NG programs. [9][10][11][12]19 Our study adds to this growing literature by comparing outcomes for infants discharged with G tubes and NG tubes to a unique reference group of infants who could have been discharged with home NG feeds but who instead remained in the NICU until achieving full oral feeding. Another unique feature of our study was the inclusion of patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing a home enteral feeding transition program in one center increased the use of NG tubes and reduced NICU length of stay. 10 In that study, as with our clinical practice, inpatient care and discharge decisions were guided by a protocol but left to clinician and family discretion. Our study extends those findings by examining the potential for additional reductions in NICU stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with recent studies in which ED visits were significantly higher among infants with GTs compared with those with NGTs. [3][4][5][6][7] Thus, bridled NGTs appear to be feasible for routine use in the pediatric outpatient setting. Bridled NGTs seem to be a suitable approach for many infants who require AHF support to discharge from the NICU but in whom GT is not desired by family or in whom the timing of surgery needs to be postponed.…”
Section: Discussionmentioning
confidence: 99%